Réponses

2014-10-12T18:00:35+02:00

B = (2/7-1/3) x (7/6-6/7)

    = (6/21-7/21) x (2/4)

    = (-1/21) x (2/4)

    = -2/84

   = -1/42


D =(-5/6 + 3/4) : (7/6 - 6/7)

   = (-20/24 + 18/24) / (49/42-26/42)

   = -2/24/13/42

   = -2/24 x 42/13

   = - 21/78

   = 7/26

Meilleure réponse !
2014-10-12T18:37:13+02:00


B= (2/7 - 1/3) x 7/4 - 5/4
  = (6/21 - 7/21) x 7/4 - 5/4
  = -1/21 x 7/4 - 5/4
  = -1/12 - 5/4
  = -1/12 - 15/12 = -16/12= -4/3

D = (-5/6+3/4):(7/6-6/7)
   = (-10/12 + 9/12):(49/42 - 36/42)
   = -1/12 : 13/42
   = -1/12 * 42/13
   = -42/156 = -7/26

Bye